Fundamentals of corporate finance / Stephen A Ross; Randolph Westerfield; Bradford D Jordan - Ross, Stephen A.
Written with one strongly held principle - that corporate finance should be developed and taught in terms of a few integrated, powerful ideas, this book has as its focus three basic themes: an emphasis on intuition; a unified valuation approach; and a managerial focus.